Trends and Topics in Computer Vision ECCV 2010 Workshops, Heraklion, Crete, Greece, September 10-11, 2010, Revised Selected Papers, Part II - Kutulakos, Kiriakos N.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The two volumes LNCS 6553 and 6554 constitute the refereed post-proceedings of 7 workshops held in conjunction with the 11th European Conference on Computer Vision, held in Heraklion, Crete, Greece in September 2010. The 62 revised papers presented together with 2 invited talks were carefully reviewed and selected from numerous submissions.The second volume contains 34 revised papers selected from the following workshops: Workshop on color and Reflectance in Imaging and Computer Vision (CRICV 2010); Workshop on Media Retargeting (MRW 2010); Workshop on Reconstruction and Modeling of Large-Scale 3D Virtual Environments (RMLE 2010); and Workshop on Computer Vision on GPUs (CVGPU 2010).
Estimating Shadows with the Bright Channel Cue -- Color-Constant Information Embedding -- Bi-affinity Filter: A Bilateral Type Filter for Color Images -- Photometric Color Calibration of the Joint Monitor-Camera Response Function -- Polyakov Action Minimization for Efficient Color Image Processing -- Color Invariant SURF in Discriminative Object Tracking -- The Narrow-Band Assumption in Log-Chromaticity Space -- Is Light Blue azzurro Color Name Universal in the Italian Language? -- Tone Correction with Dynamic Objects for Seamless Image Mosaic -- Saliency Maps of High Dynamic Range Images -- Visibility Maps for Improving Seam Carving -- Feedback Retargeting -- How to Measure the Relevance of a Retargeting Approach? -- 3D Modelling of Static Environments Using Multiple Spherical Stereo -- Hallucination-Free Multi-View Stereo -- Removing the Example from Example-Based Photometric Stereo -- iModel: Interactive Co-segmentation for Object of Interest 3D Modeling -- Automatic Registration of Large-Scale Multi-sensor Datasets -- Region Graphs for Organizing Image Collections -- Automatic Registration of Oblique Aerial Images with Cadastral Maps -- A Multi-stage Linear Approach to Structure from Motion -- Relative Bundle Adjustment Based on Trifocal Constraints -- Accurate Single Image Multi-modal Camera Pose Estimation -- An Evaluation of Two Automatic Landmark Building Discovery -- Algorithms for City Reconstruction -- Vanishing Point Detection by Segment Clustering on the Projective Space -- Effective and Efficient Image Copy Detection Based on GPU -- Really Quick Shift: Image Segmentation on a GPU Accelerated Likelihoods for Stereo-Based Articulated -- A Highly Efficient GPU Implementation for Variational Optic Flow Based on the Euler-Lagrange Framework -- From Multiple Views to Textured 3D Meshes: A GPU-Powered Approach -- Comparison of Dense Stereo Using CUDA -- Energy-Aware Real-Time Face Recognition System on Mobile CPU-GPU Platform -- Practical Time Bundle Adjustment for 3D Reconstruction on the GPU -- Accelerating Visual Categorization with the GPU -- Parallel Generalized Thresholding Scheme for Live Dense Geometry from a Handheld Camera -- Fast Organization of Large Photo Collections Using CUDA.
Keywords: Computer science; Computer software; Artificial intelligence; Computer graphics; Computer vision; Optical pattern recognition; Computer Science; Image Processing and Computer Vision; Pattern Recognition; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Computer Graphics; Information Systems Applications (incl. Internet).